Review of Pediatric Care Online. Issue 2 (3rd April 2019) - Gotschall, Terri
Abstract: Pediatric Care Online, provided by the American Academy of Pediatrics, is a point-of-care resource aimed at practicing pediatricians, nurses, and medical students. The website is an extensive resource that includes the American Academy of Pediatrics Textbook of Pediatric Care, well child resources, drug lookup, forms, news, and more. For practicing physicians, the site includes more than 250 topics in the Point-of-Care Quick Reference section, along with clinical calculators and algorithms.